Recovery as a process: Exploring definitions of recovery in the context of eating‐disorder‐related social media forums. Issue 8 (6th January 2020) - Bohrer, Brittany K.; Foye, Una; Jewell, Tom
Abstract: Objective: Online forums related to eating disorders (EDs) represent sources of support for recovery, and comments on these platforms might therefore highlight aspects of recovery that have been previously neglected in research. Reddit, an online discussion platform, hosts several ED‐related forums. Due to the unique benefits of examining ED‐related social media comments, we aimed to use a qualitative approach to conduct an exploratory study to examine users' conceptualizations of recovery from an ED. Method: We extracted public comments mentioning recovery that were posted on three ED‐related online forums on Reddit between March 2017 and August 2017. We thematically analyzed the data corpus using an inductive approach to examine how recovery is defined in the context of ED‐related online communities. Results: Two superordinate themes ("Recovery as a Process, " "Psychosocial Factors") and three subordinate themes emerged (within the "Psychosocial Factors" theme: cognitive/affective, behavioral/physical, social). Discussion: The data support a definition of recovery that includes positive aspects of well‐being and quality of life. Furthermore, the data highlight that recovery is experienced as an ongoing process that is unique to each individual.